Instructor’s Use of Social Presence, Teaching Presence, and Attitudinal Dissonance: A Case Study of an Attitudinal Change MOOC - Watson, Sunnie Lee; Watson, William R.; Richardson, Jennifer; Loizzo, Jamie (International Review of Research in Open and Distributed Learning, 2016)
This study examines a MOOC instructor’s use of social presence, teaching presence, and dissonance for attitudinal change in a MOOC on Human Trafficking, designed to promote attitudinal change. Researchers explored the MOOC instructor’s use of social presence and teaching presence, using the Community of Inquiry (CoI) framework as a lens, and examined the facilitation of attitudinal dissonance within the discussion forum, announcements and blog postings in the course. The instructor entered the MOOC with the idea of serving as a co-participant and a facilitation choice was made to address the issue of multiple perspectives and experiences. The instructional design focused on establishing a collaborative community of learners and this was demonstrated through a high number of social presence indicators but with significant use of all three areas in evidence. Findings present a detailed examination of instructor strategies in a MOOC designed to focus on the establishment of a collaborative learning community and can inform future instructional design and instruction of MOOCs in general and MOOCs for attitudinal change specifically.